Peranan Game Edukasi Kahoot Dalam Meningkatkan Motivasi Belajar Mahasiswa - Hasanah, Nida Arianda; Hafiza, Elia; Irianto, Maheswari Enesia (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research explores the impact of using Kahoot as an educational tool to increase student motivation and engagement in an academic setting. By integrating gamification elements, such as competitions, rewards, and instant feedback, Kahoot creates a dynamic and interactive learning environment that stimulates student interest and participation. With a quantitative survey research method the results of this study highlight the effectiveness of Kahoot in aligning with learning objectives, providing clear instructions, and fostering a positive learning atmosphere. Strategies to optimize motivation through Kahoot include personalizing the learning experience, promoting active participation, and celebrating student achievement. Future research directions focus on investigating the long-term impact of Kahoot, its effectiveness across different subjects, and innovative applications in educational settings.